Detrimental consequences of women life cycle on the oral cavity - Jammula Surya Prasanna; Parupalli Karunakar; M V N. Sravya; Banda Madhavi; Ambati Manasa (Wolters Kluwer Medknow Publications, 2018)
The majority of us visit a dentist only when we experience a toothache, as visiting the dentist regularly is the last thing that strikes our mind. Many clinical studies have concluded that oral bacteria can lead to a genre of health conditions which may sometimes be very serious. As females go, through certain stages in their reproductive life cycle, alterations arise in the level of sex steroid hormones circulating in their bloodstream. Specifically, variations in levels of progesterone and estrogen in women may adversely affect the periodontal tissues in the mouth. Extensive research suggests a relationship between periodontal diseases and puberty, menstruation, pregnancy, oral contraceptive use, and menopause. Estrogen and progesterone affect the entire body, including the oral tissues. The gingival tissues respond to this increased level of estrogen and progesterone by undergoing vasodilatation and increased capillary permeability. Consequently, there is an increased migration of fluid and white blood cells out of blood vessels. Also associated with increased progesterone levels are alterations in the existing microbial populations. The levels of Gram-negative anaerobic bacteria, such as Prevotella intermedia, increase as a result of the high concentration of hormones available as a nutrient for growth. This article discusses the plethora of causes which affect the oral health of women as they undergo the different life cycles.